2020
DOI: 10.48550/arxiv.2010.04176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elucidating Galaxy Assembly Bias in SDSS

Abstract: We investigate the level of galaxy assembly bias in the Sloan Digital Sky Survey (SDSS) main galaxy redshift survey using ELUCID, a state-of-the-art constrained simulation that accurately reconstructed the initial density perturbations within the SDSS volume. On top of the ELUCID haloes, we develop an extended HOD model that includes the assembly bias of central and satellite galaxies, parameterized as Q cen and Q sat , respectively, to predict a suite of one-and two-point observables. In particular, our fiduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 91 publications
1
23
0
Order By: Relevance
“…Analyses of projected galaxy two-point correlation functions (2PCFs) in the Sloan Digital Sky Survey (SDSS) show no significant evidence of galaxy assembly bias (e.g. Lin et al 2016;Vakili & Hahn 2019;Zentner et al 2019;Salcedo et al 2020). The reported strong assembly bias effect in the projected 2PCFs of massive clusters (Miyatake et al 2016) appears to be an artefact caused by an insufficient control of projection effects (Zu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of projected galaxy two-point correlation functions (2PCFs) in the Sloan Digital Sky Survey (SDSS) show no significant evidence of galaxy assembly bias (e.g. Lin et al 2016;Vakili & Hahn 2019;Zentner et al 2019;Salcedo et al 2020). The reported strong assembly bias effect in the projected 2PCFs of massive clusters (Miyatake et al 2016) appears to be an artefact caused by an insufficient control of projection effects (Zu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Halo concentration, for example, has been a popular secondary parameter Croton et al (2007a); Vakili & Hahn (2019); Kobayashi et al (2020); Wechsler & Tinker (2018); Paranjape et al (2015), although numerous recent studies have shown that the environment of the halos plays a significant role in determining the galaxy distribution (Hadzhiyska et al 2020a,c;Hadzhiyska et al 2021;Yuan et al 2020;McEwen & Weinberg 2018;Xu et al 2020;Salcedo et al 2020b,c;Abbas & Sheth 2007;Pujol & Gaztañaga 2014). There also have been multiple prescriptions for including the halo environment in the HOD model (McEwen & Weinberg 2018;Xu et al 2020;Salcedo et al 2020b,c;Yuan et al 2020;Hadzhiyska et al 2020b;Salcedo et al 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…We avoid this definition for simplicity. It can also be viewed from the related perspective of halo occupations, i.e., as the dependence of the galaxy content of haloes (occupancy variations) on halo properties beyond halo mass (see, e.g., Artale et al 2018;Zehavi et al 2018;Bose et al 2019;Salcedo et al 2020). Other definitions include the recently proposed anisotropic assembly bias, which employs higher order moments of the power spectrum (Obuljen et al 2019(Obuljen et al , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several detection claims, galaxy assembly bias is still generally regarded as an unconfirmed hypothesis (see, e.g., Miyatake et al 2016;Lin et al 2016;Sunayama et al 2016;Zu et al 2017;Montero-Dorta et al 2017;Niemiec et al 2018;Zentner et al 2019;Walsh & Tinker 2019;Sunayama & More 2019;Obuljen et al 2019;Montero-Dorta et al 2020a;Obuljen et al 2020;Salcedo et al 2020 for more information). In the context of hydrodynamical simulations, Montero-Dorta et al (2020b) showed that the halo assembly bias signal is present in IllustrisTNG and propagates to the central galaxy population when this is split by properties such as colour or SFR.…”
Section: Introductionmentioning
confidence: 99%